If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7X + 3 = -3X + -17 Reorder the terms: 3 + 7X = -3X + -17 Reorder the terms: 3 + 7X = -17 + -3X Solving 3 + 7X = -17 + -3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3X' to each side of the equation. 3 + 7X + 3X = -17 + -3X + 3X Combine like terms: 7X + 3X = 10X 3 + 10X = -17 + -3X + 3X Combine like terms: -3X + 3X = 0 3 + 10X = -17 + 0 3 + 10X = -17 Add '-3' to each side of the equation. 3 + -3 + 10X = -17 + -3 Combine like terms: 3 + -3 = 0 0 + 10X = -17 + -3 10X = -17 + -3 Combine like terms: -17 + -3 = -20 10X = -20 Divide each side by '10'. X = -2 Simplifying X = -2
| 6x^2-54+64=0 | | 9x^2+4x-1=0 | | x^5+18x^3+81x-1=0 | | (a^-3b^2/a^-5b)^1.5*(a^4b^0.25/a^-1b^2)^2 | | 11/3+3n=4/5n+18 | | 2x+6.7+4.3x-2.9-3= | | 3x-1/4y=7 | | 3x-(1/4)y=7 | | -10(-6y-3)-9= | | 5x+23=11x+27 | | 7x^5+2x^4+14x= | | 3(6-x)=9 | | x+5.97=7.16 | | 17-8=3x+16 | | 5X-9-104+20X=45-6+5X | | z/4+3=9-z/4 | | 5X-9-104+20X=46-6+9+104 | | 8g+3=5(3-5) | | (22b-2)-7(3b+3)=-7 | | -5X+8=8X-18 | | -8y+5=9y+1 | | 4x/5 | | 7X-3=3X+4 | | 5p+4=12-4p | | 13=.33y | | 27=-5-a/4 | | 80+x+46+x+66=180 | | 37+7x+3=180 | | 2+3x+130+5x=180 | | 4x^2-8x-13=0 | | 2+3x+130+5x= | | y+15=4 |